Pendampingan Usaha Asmantoga Bunga Telang Bu Mimik Berbasis Legalitas Usaha Melalui Online Single Submission (OSS) Kelurahan Medokan Ayu, Kecamatan Rungkut - Joshua Manalu; Sumainah Fauziah (Pusat Riset dan Inovasi Nasional, 2023)
Currently Micro, Small and Medium enterprises really need to have business legality. Business legality is a form of business identity that has protection from the government. However, the problem that still exists today is the lack of understanding of MSME actors about the legality of business and the large amount of social stigma about the difficulty of managing business legality because it requires a lot of documents and needs money a lot, so that some of these MSME actors are reluctant to take care of business legality. Therefore, the researchers provided assistance to one of the MSMEs in the Medokan Ayu Village, namely Asmantoga Bunga Telang Bu Mimik for managing business legality through the Online Single Submission (OSS) website. The purpose of this assistance and management is to provide education and awareness to MSME actors regarding the importance of NIB as a guarantor of business legality that is recognized by the government. The method used by researchers is preparation for registration and issuance with the expected results of this activity aimed at the business owner's knowledge of NIB as business legality. The main objective of this activity is the issuance of NIB certificates to MSME actors Asmantoga Bunga Telang Bu Mimik.